Chapters in Game Theory In honor of Stef Tijs - Borm, Peter; Peters, H.J (Springer US, 2002)
Chapters in Game Theory has been written on the occasion of the 65th birthday of Stef Tijs, who can be regarded as the godfather of game theory in the Netherlands. The contributors all are indebted to Stef Tijs, as former Ph.D. students or otherwise. The book contains fourteen chapters on a wide range of subjects. Some of these can be considered surveys while other chapters present new results: most contributions can be positioned somewhere in between these categories. The topics covered include: cooperative stochastic games; noncooperative stochastic games; sequencing games; games arising form linear (semi-) infinite programming problems; network formation, costs and potential games; potentials and consistency in transferable utility games; the nucleolus and equilibrium prices; population uncertainty and equilibrium selection; cost sharing; centrality in social networks; extreme points of the core; equilibrium sets of bimatrix games; game theory and the market; and transfer procedures for nontransferable utility games. Both editors did their Ph.D with Stef Tijs, while he was affiliated with the mathematics department of the University of Nijmegen
Keywords: Economic Theory/Quantitative Economics/Mathematical Methods; Microeconomics; Operations Research/Decision Theory; Economic theory; Operations research; Decision making; Spieltheorie; Festschrift; Aufsatzsammlung